Sintesis Silika Dari Abu Sekam Padi Termodifikasi 2-Merkaptobenzotiazol untuk Adsorpsi Ion Logam Cd2+ dan Cr6+ - Syukri, Irma; Hindryawati, Noor; Subagyono, R.R. Dirgarini Julia Nurlianti (Jurusan Kimia FMIPA UNMUL, 2017)
A study on the adsorption of Cd2+ ion using silica gel modified with 2-mercaptobenzothiazole (MBT) from rice husk ash has been conducted. The modification of silica gel with MBT was conducted by several steps namely, sample preparation, synthesis of sodium silicate and modification of silica using MBT through a sol gel method. The XRF result showed that silica gel contained 98.98 % SiO2 . The FTIR spectrum of silika MBT showed the persence of Si-OH, Si-O, Si-O-Si and –SH groups. The surface area of silica gel and silica MBT were 163 m2/g and 30 m2/g, respectively. The adsorption capacity of Cd2+ ion was 0.42 mg/g and the adsorption percentage was 69.40%. The presence of Cr6+ ion decreased the adsorption capacity of silica MBT over Cd2+ ion.